Space editor quits over fraud claims. (July 2021) - Allen, Michael
Abstract : David Baker, the editor of the British Interplanetary Society's SpaceFlight magazine, has resigned in the wake of allegations that he stretched the truth about his qualifications and professional scientific background. Michael Allen investigates